2020
DOI: 10.3390/app10031182
|View full text |Cite
|
Sign up to set email alerts
|

TLS for Dynamic Measurement of the Elastic Line of Bridges

Abstract: The evaluation of the structural health of a bridge and the monitoring of its bearing capacity are performed by measuring different parameters. The most important ones are the displacements due to fixed or mobile loads, whose monitoring can be performed using several methods, both conventional and innovative. Terrestrial Laser Scanner (TLS) is effectively used to obtain the displacements of the decks for static loads, while for dynamic measurements, several punctual sensors are in general used. The proposed sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…In [19] the authors showed that, using an interpolating curve, the precision achieved in measuring the deformation of a beam can be 20 times higher than that of a single point. These conclusions had been confirmed in [27,28]. The knowledge of the geometry of the wind tower shown in Figure 3a is needed.…”
Section: Model-based Processing Of Tls Data and Estimation Of Oscillamentioning
confidence: 76%
“…In [19] the authors showed that, using an interpolating curve, the precision achieved in measuring the deformation of a beam can be 20 times higher than that of a single point. These conclusions had been confirmed in [27,28]. The knowledge of the geometry of the wind tower shown in Figure 3a is needed.…”
Section: Model-based Processing Of Tls Data and Estimation Of Oscillamentioning
confidence: 76%
“…Applications in the field of geomatics are also proposed. The assessment of the structural health status can be performed with different geomatic techniques by means of static measurements [26][27][28] and dynamic ones [29][30][31].…”
Section: About the Present Special Issuementioning
confidence: 99%
“…This technology and its applications are certain to develop further as the rapidity and accuracy of data acquisition, and associated monitoring and modelling capabilities, become more widely recognized. Outside the BGS, ground-based LiDAR systems are used for close-range, high-accuracy applications such as bridge and dam monitoring [7], architectural restoration, crime and accident scene analysis [8], landslide and erosion mapping, forest canopy and biomass measurements [9], mobile mapping systems, adaptive cruise control systems, manufacturing, and military applications [10].…”
Section: Introductionmentioning
confidence: 99%